Metastatic multiple gastric neuroendocrine tumors with a long history of proton pump inhibitor use: A case report: Gastric neuroendocrine tumor and proton pump inhibitor usage - Erhan , Selma Şengiz; Buğra , Aytül; Keser , Sevinç Hallaç; Alemdar , Ali (Journal of Surgery and Medicine, 2022)
It is widely accepted that gastric neuroendocrine tumors (NETs) develop due to enterochromaffin-like (ECL) cell proliferation following exposure to hypergastrinemia, which causes hyperplastic-dysplastic-neoplastic changes. Here we describe the case of a 46-year-old female patient diagnosed with metastatic NETs by liver biopsy and evaluated at an external center. At our hospital, nodular structures extending from the cardia to the antrum were observed by gastroscopy, considered the primary tumor focus. Histopathological examination revealed a trabecular-insular pattern, with microNETs consisting of monotone cells with round-oval nuclei and surrounding neuroendocrine cell hyperplasia foci and fundic gland polyps. The patient had a history of regular proton pump inhibitor (PPI) use for 10 years and a serum gastrin of 9240 pg/mL. A 3-cm metastatic lesion in the left lobe of the liver was observed in whole-body imaging with octreotide. By gastrectomy, we observed a large number of nodular lesions in the corpus-antrum and a 3-cm diameter lesion in the hepatectomy material. Histopathological examination revealed NETs in multiple foci with submucosal invasion in the stomach. The Ki-67 proliferative index was 3%. Metastatic tumors of similar morphology were found in the liver and three of the greater curvature lymph nodes. We made a diagnosis of multiple gastric NETs (Grade 2). In Type I gastric NETs, the neuroendocrine cell proliferation spectrum up to NET is observed as a result of hypergastrinemia due to atrophic gastritis. Also, in experimental studies, prolonged hypergastrinemia has been reported to cause ECL cell neoplasms in animals treated with PPIs. Although our case could be accepted as Type 1 NET, the possibility of developing NET secondary to long-term PPI use should also be considered.